Buyer supplier relationship and supply chain sustainability: empirical study of Indian automobile industry. (10th September 2016) - Kumar, Divesh; Rahman, Zillur
Abstract: Over the last decade, most manufacturing organizations have been experiencing pressure to incorporate sustainability practices in their supply chains. The key reasons behind this pressure may be stated as increased consumer awareness towards environmental issues, stricter environmental laws and regulations, and increased competition. This paper seeks to identify the factors affecting sustainability adoption in the Indian automobile supply chain and investigate the inter-relationships existing among them. The factors have been identified on the basis of a comprehensive literature review and expert opinion. Data were collected through a survey of 157 Indian automobile companies; a carefully prepared questionnaire was used as research instrument. Partial least square (PLS) approach was used to investigate the relationships among various factors leading to sustainability performance. Results indicate that external influence and expected sustainability benefits positively affect top management's commitment towards adoption of sustainable practices. Further, it was found that a better buyer–supplier relationship positively impacted the triple bottom line of sustainability which comprises economic, social, and environmental performance measures. The buyer–supplier relationship was assessed after breaking it down to three constructs - supplier selection, supplier development and supplier performance review. This study is unique and carries a high originality value as it offers a better understanding of: 1) each construct (supplier selection, supplier development and supplier performance review) of the buyer–supplier relationship; and 2) every construct's effect on each dimension (economic, social and environmental) of supply chain sustainability of the Indian automobile industry. Such a comprehensive and detailed study involving the observation of each construct of the buyer–supplier relationship, and analysis of the effect that each construct has on the three dimensions of sustainability has not been carried out before. This way, the study makes a significant contribution to the existing body of literature. The present study has several practical implications which would enable managers to adopt sustainable practices in their supply chain.